Implementasi Model Pembelajaran STAD Berbantuan Media ICT Terhadap Pemahaman Konsep Matematis Siswa Kelas VIII - Faris Mawanto; Aang Yudho Prastowo; Nurul Hilda Syani Putri (Universitas Muhammadiyah Semarang, 2025)
The problem identified in this study is the inadequate understanding of mathematical concepts among students, which is thought to result from the traditional teaching methods used by educators. This research aims to explore the differences in mathematical concept comprehension among grade VIII students when using the STAD learning model integrated with ICT media, compared to the traditional STAD model. The lack of engagement in mathematics learning has led to a decline in students' interest, which, in turn, affects their understanding and mastery of mathematical concepts. This study is categorized as experimental research, specifically employing a Quasi-Experimental Design with a Pretest and Posttest Control Group Design framework. Cluster Sampling was used as the sampling method, and both test and non-test data collection techniques were applied. Data analysis involved both qualitative and quantitative methods, with statistical analysis conducted using the Independent Sample T-Test. The hypothesis testing results, performed using SPSS, showed a Sig. (2-tailed) value of 0.000, which is lower than 0.05, confirming a significant difference in the understanding of mathematical concepts between the students who received the STAD model with ICT support and those who received the traditional STAD model. Additionally, it suggests that students in the experimental group displayed a higher level of curiosity towards learning compared to those in the control group.